Hierarki Kebutuhan Dasar Tokoh Utama dalam Novel Kado Terbaik Karya J.S. Khairen - Azzahra, Hanifah; Hayati, Yenni (Persona: Kajian Bahasa dan Sastra, 2023)
The aim of this research is to describe: (1) the form of physiological needs of the main character in the novel Kado Terbaik by J.S. Khairen, (2) the form of the main character's need for security in the novel Kado Terbaik by J.S. Khairen, (3) the form of need to be loved and a feeling of love for the main character in the novel Kado Terbaik by J.S. Khairen, (4) the form of need for a sense of appreciation and respect for the main character in the novel Kado Terbaik by J.S. Khairen, and (5) the form of self-actualization needs of the main character in the novel Kado Terbaik by J.S. Khairen. The type of research used is literary research with descriptive methods. The object used in this research is the novel Kado Terbaik by J.S. Khairen. Based on the research conducted, it was found that there are 4 forms of physiological needs, 5 forms of the need for security, 4 forms of the need to feel loved and loving, 3 forms of the need for a sense of esteem and appreciation, and 1 form of the need for self-actualization of the main character in the novel Kado Terbaik by J.S. Khairen.